2011
DOI: 10.1143/jjap.50.05ea02
|View full text |Cite
|
Sign up to set email alerts
|

Role of Impurity Segregation into Cu/Cap Interface and Grain Boundary in Resistivity and Electromigration of Cu/Low-k Interconnects

Abstract: The role of impurity segregation into the Cu/cap interface and grain boundary is discussed in terms of resistivity and electromigration (EM) lifetime. A Co-based metal capping, a CuAl seed, and new liners (Ti, Zr, and Hf) are compared as technologies for EM lifetime improvement. The roles of impurity in grain growth and electron scattering are investigated by residual resistivity measurement and physical analysis. The EM lifetime distribution and activation energy of lifetime are also investigated. The efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…More specifically, atomically flat single crystal Cu(001) surfaces exhibit partially specular electron scattering with p = 0.6 if held in vacuum [23], but the scattering becomes completely diffuse (p = 0) after exposure to oxygen [24] or air [25][26][27][28], which is attributed to surface oxide formation which causes an irregular disturbance of the electron potential at the surface. [29] Electron scattering at the interface between Cu and barrier metals including Ta [4,11,12], Zr [31], Hf [31], and TiN [32] has also been reported to yield completely diffuse scattering or to cause resistivities that are even higher than what is expected for p = 0. In contrast, there are a few reports that suggest partial specular scattering at the interface between Cu and an add-layer, including scattering at the epitaxial Cu(001)/Ni(001) interface with p = 0.3 [27], Cu/SiO 2 interface with p = 0.33 [33] and a time dependent resistivity decrease for Ta and Al coated Cu which indicates increasing specularity due to oxidation of the coating [34].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, atomically flat single crystal Cu(001) surfaces exhibit partially specular electron scattering with p = 0.6 if held in vacuum [23], but the scattering becomes completely diffuse (p = 0) after exposure to oxygen [24] or air [25][26][27][28], which is attributed to surface oxide formation which causes an irregular disturbance of the electron potential at the surface. [29] Electron scattering at the interface between Cu and barrier metals including Ta [4,11,12], Zr [31], Hf [31], and TiN [32] has also been reported to yield completely diffuse scattering or to cause resistivities that are even higher than what is expected for p = 0. In contrast, there are a few reports that suggest partial specular scattering at the interface between Cu and an add-layer, including scattering at the epitaxial Cu(001)/Ni(001) interface with p = 0.3 [27], Cu/SiO 2 interface with p = 0.33 [33] and a time dependent resistivity decrease for Ta and Al coated Cu which indicates increasing specularity due to oxidation of the coating [34].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the alloy material is diffusing to the top Cu-SiCN interface to block the EM diffusion path. 12) An explanation for the different EM improvement behavior could be that Mn has a higher effective diffusion constant and is therefore moving faster to the interface compared to Al. In that case, the minimum critical Mn concentration at the Cu-SiCN interface can be reached with a lower concentration in the seed layer.…”
Section: Em Improvement Option Two: Alloysmentioning
confidence: 99%
“…[3][4][5] To overcome the issue of EM degradation, several advanced process technologies, labeled ''EM boosters'', have been proposed. However, the trade-off of improving the EM is an increase in resistivity, [6][7][8][9][10] which contributes to a temperature increase due to JH. In order to permit a higher current density limit with a long lifetime, establishing a method for evaluating JH is required.…”
Section: Introductionmentioning
confidence: 99%